The Influence of the Good Corporate Governance Towards the Value Of the Company - Aprilia Wulandari, Siti Nurlaela & Kartika Hendra Titisari (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to know the influence of good corporate governance themanufacturing sub sectors of food and drink that are listed on the Indonesia stockexchange period 2011-2016. For the measurement of the value of the company'sresearchers use the Price Earning Ratio (PER), while for corporate governanceusing the size of the Board of Directors, managerial ownership, firm size and Debtto equity Ratio (DER). The sample in this research company is a companymanufacturing sub sector of the food and drink report financial report-row take partduring the period 2011 – 2016. the results of this research show that the number ofDirectors, managerial and ownership of company size does not affect the value ofthe manufacturing companies listed on the Indonesia stock exchange period 2011-2016. Debt equity ratio effects while significantly to the value of the company.Keyword : [Good Corporate Governance, Value Company].